How easy is it to contact the duty medical doctor responsible for acute admissions?. Issue 6751 (15th September 1990) - Bakhai, A; Goodman, F; Juchniewichz, H; Martin, A; Porter, G; White, C; Williams, L; Hopkins, A
Abstract : OBJECTIVE--To ascertain ease or difficulty of contacting duty junior doctors responsible for acute medical admissions by telephone. DESIGN--Telephone survey of hospitals in six health regions in England and Wales. SETTING--70 Randomly selected hospitals, 15 of which were excluded because of non-acceptance of acute medical admissions. PARTICIPANTS--71 Duty doctors (duty house physicians, senior house officers, or registrars responsible for acute medical admissions) in 48 hospitals; seven duty doctors in seven hospitals were excluded (four declined to participate and three required a written explanation of the survey). 67 Doctors gave full information to all questions. MAIN OUTCOME MEASURES--Time taken for hospital switchboards and duty doctors to reply to telephone call, diagnoses of patients recently admitted, and on call rotas and hours of sleep of duty doctors. RESULTS--Hospital switchboards responded within 30 seconds in 87 (74%) calls, and in 76 calls (64%) the duty doctor requested was contacted within a further two minutes. Chest pain, possibly due to myocardial infarction, was the most common reason for acute medical admissions. Nearly half (48%) of the duty doctors in larger hospitals reported having 4-5 hours sleep or less on their nights on call. Most (30) were on a one in three rota; two were on a one in two rota. CONCLUSIONS--Despite impressions to the contrary contacting the duty medical team by telephone seemed fairly easy. Although most junior doctors were on a rota of one in three or better, insufficient recognition may be given to their deprivation of sleep during nights on duty.